1997
DOI: 10.1111/j.1469-7793.1997.013bi.x
|View full text |Cite
|
Sign up to set email alerts
|

Tetrodotoxin‐Sensitive Sodium Current in Sheep Lymphatic Smooth Muscle

Abstract: 1. Fast inward currents were elicited in freshly isolated sheep lymphatic smooth muscle cells by depolarization from a holding potential of -80 mV using the whole-cell patch-clamp technique. The currents activated at voltages positive to -40 mV and peaked at 0 mV. 2. When sodium chloride in the bathing solution was replaced isosmotically with choline chloride inward currents were abolished at all potentials. 3. These currents were very sensitive to tetrodotoxin (TTX). Peak current was almost abolished at 1 /,M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 18 publications
4
64
0
Order By: Relevance
“…When all of the BK current was blocked, there was a remaining voltage-dependent outward current. This was absent in cells which were dialysed with Cs¤, instead of K¤ (Hollywood et al 1997), and was reduced by TEA and 4-AP. It is highly likely, therefore, that this current was carried by K¤ ions.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…When all of the BK current was blocked, there was a remaining voltage-dependent outward current. This was absent in cells which were dialysed with Cs¤, instead of K¤ (Hollywood et al 1997), and was reduced by TEA and 4-AP. It is highly likely, therefore, that this current was carried by K¤ ions.…”
Section: Discussionmentioning
confidence: 95%
“…Although our cell yields are low, as might be expected from preparations in which the muscle layer is some 3-4 cells thick (unpublished observations) it has proved possible to obtain enough cells to allow a characterization of their membrane currents. We have demonstrated that these cells contain several inward currents (Hollywood et al 1997) and a variety of outward currents, including a Ca¥-sensitive current, and a voltage-dependent current which itself probably consists of more than one component. The Ca¥-sensitive current observed under the conditions of our experiments appears to be mediated mainly by large conductance Ca¥-activated K¤ channels (BK channels) as (1) it was sensitive to both iberiotoxin and penitrem A, which are thought to be highly selective blockers of these channels (Garcia, Galvez, GarciaCalvo, King, Vazquez & Kaczorowski, 1991;Knaus et al 1994), and (2) large channels with the characteristics of BK channels were present in inside-out patches derived from lymphatic cell membranes and, indeed, were by far the most prominent channel observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currents were recorded as previously described using the ruptured-patch configuration of the whole cell patch-clamp technique (14). Pipettes were pulled from borosilicate glass capillary tubing (1.5 mm OD, 1.17 mm ID; Clark Medical Instruments) to a tip of diameter ϳ1-1.5 m and resistance of 2-4 M⍀.…”
Section: Methodsmentioning
confidence: 99%
“…In freshly dispersed smooth muscle cells, VGSC were previously regarded as a rarity, but evidence for their existence in this cell type has been gradually accumulating. In phasic tissues, such as uterine, lymphatic, vas deferens, portal vein, and gastrointestinal smooth muscle, they may play a part in the generation and/or propagation of spontaneous electrical activity underlying myogenic contractions (14,15,29,31,38). However, they have also been found in a variety of tonic arterial smooth muscles (7,9,21,27), although mostly only in cultured cells, suggesting that they are indicative of an altered phenotype (9,27).…”
mentioning
confidence: 99%